2015
DOI: 10.1002/2014ja020625
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Pi2 pulsations in a dipole model of the magnetosphere

Abstract: Localized fast flows that impinge on the inner magnetosphere from the plasma sheet are observed to oscillate on time scales of minutes. The compression ahead of these flows will launch fast mode waves, while the velocity shears at the edges of these flows directly excite shear Alfvén waves. These waves, which are coupled by gradients in the Alfvén speed, have been suggested as a source for the Pi1 and Pi2 waves that are observed at both high and low latitudes in the ionosphere. A new three-dimensional simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 59 publications
1
52
0
Order By: Relevance
“…As the waves pass through the plasma sheet boundary layer (PSBL) or near the Earth, they encounter both strong density and field gradients, where the fast compressional mode will covert to the shear Alfvén mode. The fast‐Alfvén mode conversion in the PSBL and the magnetic lobes was also observed in Polar satellite data [ Keiling et al , ] and MHD simulations [ Allan and Wright , ; Lysak and Song , ; Lysak et al , ].…”
Section: Resultsmentioning
confidence: 60%
“…As the waves pass through the plasma sheet boundary layer (PSBL) or near the Earth, they encounter both strong density and field gradients, where the fast compressional mode will covert to the shear Alfvén mode. The fast‐Alfvén mode conversion in the PSBL and the magnetic lobes was also observed in Polar satellite data [ Keiling et al , ] and MHD simulations [ Allan and Wright , ; Lysak and Song , ; Lysak et al , ].…”
Section: Resultsmentioning
confidence: 60%
“…We found that the B z power is a decreasing function of latitude, whereas B x and B y powers are increasing functions. According to numerical studies of plasmaspheric resonances (Lysak et al, 2015;Teramoto et al, 2011), the compressional wave trapped in the plasmasphere is confined in a dipole latitude rage of −40 • < MLAT < 40 • . The cross phases between B z and H are distributed near 0 • without depending on the latitude of the satellite, whereas the B x − H cross phases are near 0 • in the Northern Hemisphere and about 180 • in the Southern Hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lysak et al [2015] have investigated propagation of a damped sine wave with about 1 min period from the near-Earth plasma sheet (X ≈ −10 R E ) down to the low-altitude ionospheric boundary placed at 100 km. They have revealed that ULF waves can propagate through the inner magnetosphere, and a compressional pulse at −10 R E can excite both shear-mode field line resonances and fast-mode plasmaspheric resonances.…”
Section: Discussionmentioning
confidence: 99%